2006
DOI: 10.1128/jb.00564-06
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Vibrio cholerae Integration Host Factor in Conjugative DNA Transfer

Abstract: The requirement for host factors in the transmission of integrative and conjugative elements (ICEs) has not been extensively explored. Here we tested whether integration host factor (IHF) or Fis, two host-encoded nucleoid proteins, are required for transfer of SXT, a Vibrio cholerae-derived ICE that can be transmitted to many gram-negative species. Fis did not influence the transfer of SXT to or from V. cholerae. In contrast, IHF proved to be required for V. cholerae to act as an SXT donor. In the absence of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…In the V. cholerae El Tor strain N16961, McLeod et al have found that, as in E. coli and Salmonella strains (2,33), over 100 genes are differentially regulated in an ihfA mutant (34). In the work presented here, we show that IHF positively influences the expression of virulence genes in the V. cholerae classical O395 strain.…”
Section: Discussionsupporting
confidence: 57%
“…In the V. cholerae El Tor strain N16961, McLeod et al have found that, as in E. coli and Salmonella strains (2,33), over 100 genes are differentially regulated in an ihfA mutant (34). In the work presented here, we show that IHF positively influences the expression of virulence genes in the V. cholerae classical O395 strain.…”
Section: Discussionsupporting
confidence: 57%
“…On one hand, ImmR was shown to bind diverse loci in the chromosome of B. subtilis, which could have a significant impact on host gene expression, and consequently on the fitness of the organism (78). On the other hand, several studies have reported the implication of host factors in the modulation of ICE dynamics, in both Grampositive and Gram-negative bacteria (48,90,91). At least three host factors are known to influence ICEBs1 mobility.…”
Section: Immr/imma As a Central Regulatory System Of Icebs1mentioning
confidence: 99%
“…Therefore, excision is not a rate-limiting step of SXT transfer. The host encoded nucleoid associated protein IHF (integration host factor), which is necessary for integration and excision of the bacteriophage λ in E. coli, is not required for SXT integration into or excision from the V. cholerae chromosome (48).…”
Section: Integration and Excisionmentioning
confidence: 99%
“…This has been shown for SXT elements in Vibrio cholerae, which require the host factors IHF and Fis for excision, recombination, and conjugation (53). Host factors may be chromosomally encoded and not on the MGE itself, leading to the inability of the MGE to conjugate in their absence.…”
Section: Resultsmentioning
confidence: 99%